Entrepreneurial Self-Efficacy and Entrepreneurial Intention of University's students: the impact of entrepreneurial learning / Rohana Ngah, Abang Zainoren Abang Abdul Rahman and Siti Zahrah Buyong. - Ngah, Rohana; Abang Abdul Rahman, Abang Zainoren; Buyong, Siti Zahrah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Assessing the entrepreneurial intention among students has been an interest and focus of researchers and policy makers in promoting and nurturing graduate entrepreneurs. Recent studies on entrepreneurial intention (EI) have included entrepreneurial self-efficacy (ESE) as one of the important factors that influence students to take up entrepreneurship as one of employment alternatives. Higher Education Institutions (HEIs) have taken initiatives to embed entrepreneurship elements in the curriculum as well as actively organize continuous entrepreneurial activities to impart entrepreneurial learning. The objectives of this paper are to explore the relationship of Entrepreneurial Self-Efficacy (ESE) and Entrepreneurial Intention (EI) and also to investigate the impact of Entrepreneurial Learning (EL) as mediator. The findings show that ESE has a strong and positive direct impact on students' EI; however, EL does not mediate the relationship of ESE and EI. Implication of these findings for entrepreneurship research and learning are discussed.